Linear Interpolation Using Siemens S7-1200 - Noppadol Maneerat; Tharathorn Wongworrada; Thepjit Cheypoca; Kasemsuk Sepsirisuk (My University, 2025)
This research is a continuation of the research on circular interpolation use siemens s7-1200 [1] It presents the movement of 3 axes, $x y z$, as a method of moving in a curve that is controlled by programmable logic control (PLC). In the future research, PLC will be used to control linear movement straightly. The work will be in the original format, but change the equation used to move in a straight line instead.
Keywords: Sensor Technology and Measurement Systems